Design and evaluation of structural risk mitigation measures for transmission lines micro-pile foundations in mountainous region - Xin Hu; Xiaojuan Xi; Zijun Xiang (PLoS ONE, 2026)
Influenced by the complex geological conditions in mountainous region, micro-pile foundation for transmission line faces the risk of insufficient bearing performance. It is important to study the risk suppression measures of micro-pile foundation and its assessment method to promote the construction of transmission lines in mountainous regions. Firstly, the mechanical simulation model of pile-soil system for the micro-pile foundation is established in this paper, and the field test is carried out to verify the accuracy of the simulation model, thus the ultimate load of the micro-pile foundation is determined according to the current code requirement for maximum displacement in case of damage to the group pile foundation. Secondly, to address the subjectivity of traditional methods, an improved Likelihood-Exposure-Consequence (LEC) method is proposed. Its novelty lies in constructing a quantitative displacement-risk mathematical mapping, directly linking the physical limit state (maximum displacement) to the risk likelihood factor. Thirdly, structural risk reduction measures for the micro-pile foundation using micro-expanded pile foundation and micro-inclined pile foundation are proposed, and the ultimate load of the traditional micro straight pile foundation is used as an excitation to carry out the simulation of the bearing performance of the two improved micro-pile foundations, and the maximum displacements of the two improved micro-pile foundations are calculated. Finally, based on the proposed improved LEC method, the risk values-defined in the LEC framework as the quantitative product of Likelihood ( L ), Exposure ( E ), and Consequence ( C )-and risk classes of the two improved micro-pile foundations are calculated and compared with the conventional micro straight pile. The results demonstrate that the proposed strategies significantly reduce the safety risk class, providing a robust, quantifiable basis for optimizing foundation designs in complex mountainous terrain.